1992
DOI: 10.1103/physrevlett.69.2384
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a prewetting transition during surface melting of caprolactam

Abstract: The surface-induced melting of the close-packed (100) face of the anisotropic molecular crystal caprolactam has been studied using x-ray reflectivity. A thin-to-thick film prewetting transition is observed at about 13 K below the bulk melting point. Only above this transition does the thickness of the quasiliquid layer increase continuously with temperature. We speculate that initially the surface melting proceeds via layering transitions. PACS numbers: 64.70.Dv, 68.35.Rh, 68.45.GdThe experimental observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…3 The second is an x-ray study of the ͑001͒ surface of caprolactam ͑C 6 H 11 ON͒, which exhibited behavior similar to surface melting. 4 In the present investigation, we have repeated the original experiment under more controlled conditions, and shown that the observed phenomenon is inconsistent with surface melting. Further, we propose a surface hydration mechanism that can account for all the empirical observations.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…3 The second is an x-ray study of the ͑001͒ surface of caprolactam ͑C 6 H 11 ON͒, which exhibited behavior similar to surface melting. 4 In the present investigation, we have repeated the original experiment under more controlled conditions, and shown that the observed phenomenon is inconsistent with surface melting. Further, we propose a surface hydration mechanism that can account for all the empirical observations.…”
mentioning
confidence: 64%
“…In order to reconcile these findings with those of Ref. 4, we must consider other explanations for the observed behavior of the wetting layer, in addition to surface melting. Effects related to sample impurity, for example, may be a possible alternative interpretation of the data.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The density-functional models have been refined and extended [3][4][5][6][7] and supported by computer simulations [8][9][10][11][12][13][14][15] as well as experiments. [16][17][18] For a review of wetting and prewetting, see ref 19.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray reflectivity measurements were used for high-temperature studies of the (100) face of caprolactam (C 6 H 11 ON) [5,6]. Initially a series of layering transition followed by prewetting was suggested, but later a surface hydration mechanism was proposed for temperature disordering of this surface.…”
Section: Introductionmentioning
confidence: 99%